Razmere na področju klasičnega šolstva v obdobju 1945-1958 - Hriberšek, Matej (Monitor ISH, 2005)
The situation of the classical schools in the years 1945-1958. After the end of World War II, the classical school system in Slovenia began its slow but the classical gymnasium as its central institution, came under fire. The classical education was not allowed, or perhaps not able, to carve itself a niche in the new political system. Despite their efforts to preserve the teaching of the classical languages, despite the many conferences and consultations dedicated to this problem, the pleaders for Latin and Greek were not successful; both languages were reduced substantially. The campaign against the classical languages culminated in 1958, when classical gymnasia were abolished.
Keywords: Latin; latinščina; grščina; šolstvo; school; gimnazije; klasična gimnazija; zgodovina šolstva; Slovenia; Slovenija